Indoor tracking from multidimensional sensor data - Moreira, Adriano (2016)
Tracking the position of people or vehicles in large indoor settings with high accuracy is still a challenge despite the significant progress observed in indoor positioning technology in the last decade. To date, there is not a clearly dominant indoor positioning solution for general use, and challenges related to seamless indoor-outdoor positioning, reliable floor estimation and indoor maps are still needing more research. In this context, the IPIN 2016 conference is promoting a competition to evaluate a set of competing indoor positioning solutions in a realistic scenario. This paper describes the proposal of the UMINHO team and some of the obtained results.